Dirāsah Taqābuliyyah Baina Al-Lughah Al-‘Arabiyyah Wa Al-Lughah Al-Indūnīsiyyah ‘Alā Mustawā Al-Khabar - Zamzam Zamaludin; Said Hassan Nassila (Mauriduna: Journal of Islamic Studies, 2021)
تهدف هذه الدراسة إلى معرفة الخبر في اللغة العربية وفي اللغة الإندونيسية، وهناك أمران أساسيان، أولهما: اكتشاف أوجه التشابه والاختلاف بينهما من الناحية الصرفية، والنحوية، والدلالية، وثانيهما: إعداد محتويات الدرس لتعليم اللغة العربية على مستوى الخبر للإندونيسيين المبتدئين بناء على نتائج هذه الدراسة التقابلية. وقد استخدمت هذه الدراسة المنهج الوصفي التحليلي للوقوف على خصائص الخبر بين اللغة العربية واللغة الإندونيسية، واستخدمت منهج التحليل التقابلي لمقارنة الخبر بين اللغتين ولاستنباط أوجه التشابه والاختلاف بينهما. وتوصلت إلى نتيجتين مهمين، أولاهما: وجود تشابه واختلاف بين اللغتين من الناحية الصرفية، والنحوية، والدلالية، وثانيتهما: أنه يمكن الاستفادة من نتائج هذه الدراسة لإعداد دروس بطريقة مناسبة لتعليم اللغة العربية على مستوى الخبر للإندونيسيين المبتدئين. This study aims to determine the predicate in Arabic and Indonesian, there are two core objectives of this study, first is to deal with the similarities and differences between the terms in terms of morphology, syntax and semantics, and the second is to propose Khobar teaching methods for Indonesian students beginner level based on the results of contrastive studies. This study uses descriptive analysis method to identify the characteristics of predicates in Arabic and Indonesian, and uses a comparative analysis method to compare the predicate between Arabic and Indonesian and reveal the similarities and differences in both. There are two results of this study, the first is the similarities and differences between the predicate Arabic and Indonesian in terms of morphology, syntax and semantics, and the second is the results of this study can be used to prepare teaching materials and teaching methods Khobar for Indonesian level students a beginner.